The Ongoing Revolution in Breast Imaging Calls for a Similar Revolution in Breast Pathology. (24th September 2012) - Tabár, L.; Dean, P. B.; Lindhe, N.; Ingvarsson, M.
Abstract : Communication between pathologists and radiologists suffers from a lack of common ground: the pathologists examine cells in ultrathin tissue slices having the area of a postage stamp, while the radiologists examine images of an entire organ, but without seeing the cellular details. The current practice of examining breast cancer specimens is analogous to scrutinizing individual pieces of a jigsaw puzzle, without examining all of them and never putting all the pieces into place. The routine use of large section histopathology technique could help to alleviate much of this problem, especially with nonpalpable, screen-detected breast cancers. The study of three-dimensional (3D) images of subgross, thick section pathology specimens by both radiologists and pathologists could greatly assist in the communication of findings.